In silico integrative analysis of multi-omics reveals regulatory layers for diurnal gene expression in mouse liver - Jiang, Chunjie; Liu, Panpan; La, Cam Mong; Guan, Dongyin (Frontiers in Endocrinology, 2022)
Diurnal oscillation persists throughout the body and plays an essential role in maintaining physiological homeostasis. Disruption of diurnal rhythm contributes to many diseases including type 2 diabetes. The regulatory mechanism of the transcription-translation feedback loop (TTFL) of core clock genes is well-established, while a systematic study across all regulatory layers of gene expression, including gene transcription, RNA translation, and DNA binding protein (DBP) activities, is still lacking. We comprehensively bioinformatics analyzed the rhythmicity of gene transcription, mature RNA abundance, protein abundance and DBP activity using publicly available omic datasets from mouse livers. We found that the core clock genes, Bmal1 and Rev-erba, persistently retained rhythmicity in all stages, which supported the essential rhythmic function along with the TTFL. Interestingly, there were many layer-specific rhythmic genes playing layer-specific rhythmic functions. The systematic analysis of gene transcription rate, RNA translation efficiency, and post-translation modification of DBP were incorporated to determine the potential mechanisms for layer-specific rhythmic genes. We observed the gene with rhythmic expression in both mature RNA and protein layers were largely due to relatively consistent translation rate. In addition, rhythmic translation rate induced the rhythms of protein whose mature RNA levels were not rhythmic. Further analysis revealed a phosphorylation-mediated and an enhancer RNA-mediated cycling regulation between the corresponding layers. This study presents a global view of the oscillating genes in multiple layers via a systematical analysis and indicates the complexity of regulatory mechanisms across different layers for further functional study.